O trabalho dos camponeses e a produção não-capitalista no assentamento 16 de Maio Ramilândia/PR - Gonçalves, Leandro Daneluz (2013)
This research is about the peasant labor in "May 16" settlement located in the municipality of Ramilândia / PR. This settlement was the result of the struggles undertaken by landless to acquire its territory, such cases are very common in Brazil. The conflicts of interest occur between landowners and/or capitalists and landless peasants, through the struggles and resistance, gradually the landless peasants get the consolidation and conquest of a settlement. In the settlement, the landless construct and reconstruct their condition of peasants, which highlights the work relationships within the family production. Although the work peasant is subordinate to capital, it has characteristics which differ from that done by workers in a factory, for example. It also differs workers that keep poor relations, typical of a flexible capital accumulation. Thus, the work presents peasant features non-capitalist, although serving and is inserted into the overall process of capitalist accumulation. The division of labor, time control, mutual help, payment for work, solidarity work , reciprocity, exchange of operational days inside of peasant production unit, in this case the "May 16" settlement, are features that work in non-capitalist peasant stands.